2015
DOI: 10.1371/journal.pone.0139548
|View full text |Cite
|
Sign up to set email alerts
|

Efferent Vestibular Neurons Show Homogenous Discharge Output But Heterogeneous Synaptic Input Profile In Vitro

Abstract: Despite the importance of our sense of balance we still know remarkably little about the central control of the peripheral balance system. While previous work has shown that activation of the efferent vestibular system results in modulation of afferent vestibular neuron discharge, the intrinsic and synaptic properties of efferent neurons themselves are largely unknown. Here we substantiate the location of the efferent vestibular nucleus (EVN) in the mouse, before characterizing the input and output properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 82 publications
(97 reference statements)
5
21
0
Order By: Relevance
“…Recent electrophysiological characterization of EVN neurons revealed heterogeneous synaptic input (Mathews et al . ) consistent with polysynaptic tracing work demonstrating connections between the EVN and many other brain structures including the flocculus (Metts et al . ).…”
Section: Introductionsupporting
confidence: 86%
“…Recent electrophysiological characterization of EVN neurons revealed heterogeneous synaptic input (Mathews et al . ) consistent with polysynaptic tracing work demonstrating connections between the EVN and many other brain structures including the flocculus (Metts et al . ).…”
Section: Introductionsupporting
confidence: 86%
“…Cholinergic EVN neurons were identified in one study using transgenic mice engineered to express enhanced green fluorescent protein (eGFP) under the choline-acetyltransferase (ChAT) promotor (Leijon and Magnusson, 2014 ). In another study, the location of EVN neuronal recordings were confirmed using retrograde tracing from the posterior semicircular canal in ChAT:: tdTomato transgenic mice which confirmed the location of cholinergic EVN neurons, and the staining of each recorded neuron (Mathews et al, 2015 ). Both studies were conducted in vitro .…”
Section: Physiology Of Evn Neuronsmentioning
confidence: 80%
“…However, the mammalian EVS can possess multiple groups, dependent on species. Mouse and cat have only one cluster of EVN neurons, located near the facial nerve genu (Warr, 1975 ; Leijon and Magnusson, 2014 ; Mathews et al, 2015 ). In other mammalian studies, more than one cluster was observed with the major nucleus being referred to as group e (Goldberg and Fernàndez, 1980 ), located dorsal and/or ventral to the facial nerve (Shumilina et al, 1986 ; Perachio and Kevetter, 1989 ).…”
Section: Anatomy and Morphology Of The Evs Across Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that cochlear efferents have to be stimulated at least at 10 Hz to facilitate their normally low probability of release (Ballestero et al, 2011), and it is a reasonable assumption that the same is required for vestibular efferents. Vestibular efferents in mouse brainstem slices (Leijon and Magnusson, 2014;Mathews et al, 2015Mathews et al, , 2017 have spontaneous resting discharges of up to 5 spikes/s. The main input to efferent neurons is provided by the vestibular nuclei, and the spontaneous activity of vestibular nuclei neurons is ϳ5 times higher in alert mice (57.5 Ϯ 4.2 spike/s) (Beraneck and Cullen, 2007) compared Figure 8.…”
Section: Discussionmentioning
confidence: 99%